Development of E-LKM on Colloid Materials Based on Science Technology and Society to Improve Creative Thinking Skills - Melinda Sari; Okta Suryani; Mawardi (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop E-LKM based on Science Technology Society (STS) on colloid material and analyze its validity and practicality in improving students' creative thinking skills. The method used in this research is Research and Development (R&D) with the 4D model, but this research is limited only to the development stage, namely validity and practicality tests. The define stage was carried out by analyzing student needs, curriculum, and relevant colloid concepts. At the design stage, the E-LKM was designed by integrating the STS model. The develop stage includes validation by a team of five experts and practicality testing by two lecturers and Chemistry Education students. The research instruments consisted of interviews, questionnaires, validation sheets, and practicality instruments. The results of the validity test using Aiken's V in terms of material and media obtained 0.89 and 0.93 in the valid category. The results of the practicality test conducted by lecturers and students were 90.15% and 92% with a very practical category. The assessment was carried out based on four aspects of creative thinking: fluency, flexibility, originality, and elaboration, which showed an increase after the use of E-LKM. The results of this study prove that the STS-based E-LKM on colloid material is valid and practical and has the potential to improve students' creative thinking skills. Further research can examine its effectiveness in understanding chemical concepts and its application to other topics